Teologi Trauma: Trauma Pada Anak Dampak Dari Perceraian Orangtua - Siahaan, Lucius; Zulkarnain; Barus, Pris Vaelentino (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2024)
Divorce is rarely seen as a way out of various household problems. Divorce is not the right solution to resolve the conflict; of course, a divorce can hurt others, especially the child; the divorce of parents can cause trauma to the child. In fact, the wounds that a child may have suffered will probably continue to carry it to adulthood; The impact on each child may vary, depending on the child's age at the time of the parents' divorce, the circumstances of the divorce, and the personality of the child. When a divorce occurs within a family, the child is the primary victim who is most affected by the negative impact of the divorce; The purpose of this writing is to explain that divorce is a phenomenon of social change taking place in today's society; divorce results in damage to relationships between family members that do not support the growth and development of the child; divorces cause family dysfunction; divorcing creates an emotional distance between the child and the parent; and divorce can also result in trauma to the child. The author uses a qualitative method to analyze this research problem using interviews and literature.